2015
DOI: 10.1108/jsbed-09-2011-0006
|View full text |Cite
|
Sign up to set email alerts
|

The composition of employment in new innovative firms

Abstract: Purpose – The paper explores the composition of employment in new innovative firms. The purpose of this paper is to shed some light on the mixture of job positions at the firm level measured by employees’ occupational position, their qualification and specialisation, as well as their origin. As there is little known about the structure and quality of employment in new firms, insights are helpful for policymakers who are engaged in regional development and job creation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Prior studies such as Mbuyisa and Leonard (2017), Bogliacino and Pianta (2009), Wadho et al (2019), Olurinola et al (2021), Karakara and Osabuohien (2020), Matthew et al (2020), Lautenschläger (2015), Zhu et al (2021) and Aloisi and De Stefano (2020) have taken into consideration the importance of innovation to drive firm's growth as job creation or employment. According to Mbuyisa and Leonard (2017), innovation brings various opportunities for entrepreneurs to improve their business outcomes, attain growth, retain profitability and contribute to employment creation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies such as Mbuyisa and Leonard (2017), Bogliacino and Pianta (2009), Wadho et al (2019), Olurinola et al (2021), Karakara and Osabuohien (2020), Matthew et al (2020), Lautenschläger (2015), Zhu et al (2021) and Aloisi and De Stefano (2020) have taken into consideration the importance of innovation to drive firm's growth as job creation or employment. According to Mbuyisa and Leonard (2017), innovation brings various opportunities for entrepreneurs to improve their business outcomes, attain growth, retain profitability and contribute to employment creation.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Emera (2021) found that innovation shocks negatively affect a firm's employment capacity. On the contrary, Lautenschläger (2015) found no evidence that innovative firms contribute to combating structural unemployment, at least in the short‐run. Bhattacharyya and Mitra (2020) found inadequate extensive evidence on the impact of innovation on total factor productivity growth.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies emphasize that innovation potential in an enterprise could be additionally supported by the higher educational attainment of the labor force. R&D performing firms and especially academic spin-offs are more prone toward hiring employees with university degrees in comparison to employees with professional education [33]. Related to the access to finance perceptions, higher education of the employees could be related to the better understanding of the financing application procedures [31].…”
Section: Data and Empirical Strategymentioning
confidence: 99%